Schwannosis in Three Foals and a Calf. Issue 5 (September 2019) - Miranda, Ileana C.; Taylor, Kyle R.; Castleman, William; de Lahunta, Alexander; Summers, Brian A.; Miller, Andrew D.
Proliferation of ectopic Schwann cells within the central nervous system (CNS) parenchyma (schwannosis) in early life is most commonly associated with human neurofibromatosis type-2 and has been unrecognized in domestic animals. Three foals and a calf, 5 to 11 weeks old, with progressive neurological signs from birth were studied. Histologically, at multiple levels of the spinal cord, all animals had bilateral plaques of proliferative spindle cells, predominantly affecting the white matter adjacent to dorsal and ventral nerve roots and variably extending into the gray matter. Proliferating cells had strong intracytoplasmic immunoreactivity for the Schwann cell markers myelin protein zero and periaxin, highlighting the formation of peripheral nervous system (PNS) myelin within the spinal cord. In all cases, foci of disorganized neural tissue (glioneuronal hamartomas) were present, which in 2 cases formed a mass effect that resulted in syringohydromyelia. Neonatal presentation suggests a congenital maldevelopment of the nervous system, with spontaneous invasion of PNS-derived Schwann cells into the CNS.